Elastase Activity of Representatives of the Genus Bacillus Isolated from the Coastal Area of the Kinburn Split - Gudzenko, O.V.; Varbanets, L.D.; Гудзенко, О.В.; Варбанець, Л.Д. (PH "Akademperiodyka" of the NAS of Ukraine, 2024)
Previously, elastase activities have been found in some microorganisms and presented by metalloproteases, which may play an important role in helping bacterium invasiveness and establishment of infection. The elastases from Bacillus species are serine proteases, however, to date there are few reports on systematic study of these enzymes producers among representatives of Bacillus, as well as studies of their properties. The aim of this work was to study some physicochemical characteristics of partially purified elastase enzyme from a number of Bacillus sp. strains. Methods. The objects of the study were strains of Bacillus sp. (L1, L2, L9) isolated from the dry grass of the coastal zone of the Kinburn split (Mykolaiv region). Cultures were grown under submerged cultivation at 28 °С, with a shaking speed of the nutrient medium of 230 rpm for 2 days. Methods of determining elastase activity in the culture liquid supernatant were used. Results. It has been shown that Bacillus sp. L9, L1, and L2 are characterized by high levels of elastase activity (35.80, 28.0, and 33.80 U/mL, respectively). The maximum synthesis of elastase occurs on the second day of cultivation of the producer at 28 °C and shaking at 230 rpm. Maximum hydrolysis of elastin by Bacillus sp. L1 and L2 are carried out at  40 °C but at different pH optima. Thus, for the preparation of Bacillus sp. L1, optimal pH is 8, and for L2 – 10. For the complex enzyme preparation of Bacillus sp. L9, maximum hydrolysis of elastin occurs at pH 9 and temperature 50 °C. Conclusions. Bacillus sp. L9 with elastase activity is promising for continued research on its properties for further practical use.